Marine and terrestrial foods as a source of brain-selective nutrients for early modern humans in the southwestern Cape, South Africa. Issue 97 (August 2016) - Kyriacou, K.; Blackhurst, D.M.; Parkington, J.E.; Marais, A.D.
Abstract: Many attempts have been made to define and reconstruct the most plausible ecological and dietary niche of the earliest members of the human species. While earlier models emphasise big-game hunting in terrestrial, largely savannah environments, more recent scenarios consider the role of marine and aquatic foods as a source of polyunsaturated fatty acids (PUFA) and other brain-selective nutrients. Along the coast of southern Africa, there appears to be an association between the emergence of anatomically modern humans and accumulation of some of the earliest shell middens during the Middle Stone Age (200–40 ka). Fragmentary fossil remains classified as those of anatomically modern humans, along with marine food residues and numerous material cultural indicators of increased social and behavioural complexity have been recovered from coastal sites. In this paper, new information on the nutrient content of marine and terrestrial foods available to early modern humans in the southwestern Cape is presented and compared with existing data on the nutritional value of some wild plant and animal foods in Africa. The results suggest that coastal foraging, particularly the collection of abundant and predictable marine molluscs, would have allowed early modern humans to exploit some of the richest and most accessible sources of protein, micronutrients and longer-chain omega-6 and omega-3 fatty acids. Reliable and accessible sources of omega-3 eicosapentaenoic and docosahexaenoic acid are considerably more restricted in terrestrial foods.